Le talent ne fructifie pas dans l’oisiveté : une Française dans la Révolution cubaine - Sylvie Bouffartigue (Caravelle)
As an immigrant to Cuba in 1957, Wanda Lekszycka, a french academic immersed in intellectual and artistic life, reveals through her notebooks and diaries a personal, intimate, passionate and original vision of Havana and the Revolution.